UNLOCKING THE LIVES OF HUMAN BOOKS: SHARING VIDEOS TO INSPIRE PEOPLE HIDING IN THE SHADOWS - Yap, Joseph M. (UIN Sunan Kalijaga Yogyakarta, 2021)
Human books voluntarily share their life stories with readers to let them understand what they are going through and how they survived their struggles. Speaking up may not be easy for them yet their courage to break stereotypes thrown upon them will be much recognized and accepted in an open and decent dialogue. Just like any other library programming events, human libraries are vividly documented in photographs, videos, social media, newsletters, and activity reports. This research study seeks to explore the role of video sharing sites as a tool to promote library events, specifically human libraries. Existing uploaded playlist videos pertaining to human libraries hosted by academic and public libraries will be the focus of this paper.
Keywords: human library; human books; stereotypes; social cohesion; YouTube